On singularities of the Galilean spherical darboux ruled surface of a space curve in $G_3$ - Şahin, T.; Yilmaz, M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We study the singularities of Galilean height functions intrinsically related to the Frenet frame along a curve embedded into the Galilean space. We establish the relationships between the singularities of the discriminant and the sets of bifurcations of the function and geometric invariants of curves in the Galilean space.